Foreign Direct Investment and Economic Growth: The Nigerian Context - Henry, Enyi Chika; Adeyinka, Ibianga Gift (Research Parks Publishers, 2024)
Despite the flow of FDI in Nigeria, there is still high rate of unemployment, leading to greater level of insecurity, banditry, kidnapping etc. Until adequate economic investments are actualized, it will be difficult to achieve and measure both human and material resources. The study investigated the relationship between foreign direct investment and economic growth in Nigeria using ex-post-facto research design. The time series data used covered the time period 1990-2022. The data were obtained from the Annual Statistical Bulletin of the Central Bank of Nigeria. The population for this study consists of the national economic data that is pertinent to this research. However, this limitation applies specifically to foreign direct investment, which includes both oil and non-oil foreign direct investment, as well as economic growth measured by real gross domestic product (RGDP). In line with the positivist investigation ethic and quantitative design, this study use parametric statistics as the technique for inferential analysis. This technique involves the utilisation of quantitative models to determine the connection between two variables. It uses sample-based parameters as metrics to make inferences about the population being studied. The analysis was conducted with linear regression. The analysis confirmed a substantial correlation between characteristics related to foreign direct investment and economic growth. Consequently, the study demonstrated a substantial and favourable correlation between variables related to foreign direct investment and economic growth. Hence, the study recommends that policymakers should formulate policies that both encourage foreign investment and safeguard and enhance domestic production and investment. These policies should align with the development objectives of the host countries. The Nigerian government should prioritise substantial investments in non-oil sectors like agriculture and mining to generate a multiplier effect and boost the productive capacity of non-oil exports. This will contribute to the long-term economic growth and sustainability of Nigeria.